Distance education project of English idioms learning from watching YouTube - Vongpumivitch, Viphavee; Yu, Li-Tang; Nguyen, Thuy Phuong (Frontiers in Psychology, 2023)
Idioms have been recognized to be commonly adopted by academic practitioners in their speech and writing. However, regardless of their common occurrence in English communication, idioms pose great challenges for non-native English speakers, as they are often ignored in English classrooms. Particularly in Vietnam, a minimal number of idioms appear in English textbooks published by the Ministry of Education, and teachers appeared to under-emphasize English idioms’ usefulness in conversation. To fill the gap, the present study adopted YouTube for Vietnamese students to undertake supplementary learning of English idiom knowledge. The study recruited 34 students and randomly assigned them to a control group and an experimental group. Both groups were required to take notes during their watching. Yet, only the experimental group would take extra exercises at the end of their watching. Immediate post-tests, delayed post-tests, and a survey were conducted. The findings demonstrate that the students in the two groups retained idiom knowledge similarly well. They were also positive towards learning English idioms through YouTube. Pedagogical implications and research suggestions are provided to conclude the study.